O группах Фробениуса с неинвариантным множителем SL₂(3) - Козулин, С.Н.; Сенашов, В.И.; Шунков, В.П. (Український математичний журнал, 2006)
Отримано ознаку непростоти нeскiнчeннoi групи, що мютить нeскiнчeнний клас труп Фробешуса Lg=⟨a,g⁻¹ag⟩ з доповненням SL₂(3). We obtain a criterion for the unsimplicity of an infinite group containing the infinite class of the Frobenius groups Lg=⟨a,g⁻¹ag⟩ with complement SL₂(3).